Analysis Of Implementation Of Communicative Approach In Teaching English Under “Kurikulum Merdeka” - Sujinem (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
Nowadays communities are increasingly facing rapid and profound changes and tensions that affect the social, economic, and political aspects of life. The role of education has also become questionable in the millennial era. A matter of fact, 21st century education requires a gradual shift in curriculum construction focusing on the transferable competencies that learners need to develop in instructional settings. Communication is the real proof of an English competency. In today’s knowledge–based, types of skills and competencies that students need to gain are different from in the past. Emphasizing the communicative competence is one of the most influential developments in language education. The implementation of communicative activities in EFL/ESL classroom prepares learners to use English in the world beyond based on their own needs, interests and opportunities. This article was aimed to analyze of the implementation of Communicative Approach (CA) in Teaching English under Kurikulum Merdeka. The data was collected from various journals of teaching English and articles online in internet The results have shown that Communicative Approach (CA) in Teaching English especially in the Speaking lesson is compatible and promising. Keywords: Communicative Approach (CA), Teaching English, Kurikulum Merdeka.